A Scientific and Analytical Study of Seretagrams in Pashto Nasr (Selected books in Sīrah Light) - Shaibar,; Ata ur Rahman, (Journal of Islamic and Religious Studies, 2019)
Due to the significance of Sīrah, Muslim scholars started writing about it from the very beginning of Islam. Pashto language, like other major languages, contains the Sīrah writings. There are two types of Sīrah writings in Pashto language. The first type of books are written for a common man, in a very simple language and style, just to get guidance from the Sīrah of the Holy Prophet (P.B.U.H). This type of books were discussed by Dr. Sa’īdullah Qaḍī in his article “Sīrah books in Pashto Language” published in “Al-Ḥaq” Monthly Journal of Jami’a Dārul Uloom Ḥaqqānia, Akora Khattak. The second type of Sīrah books are written after deep research and criticism of the narrations. But it is worth mentioning that no comprehensive research has been carried out so far which can cover both types of books. Therefore an analysis of the Selected Sīrah writings in Pashto Language has been made, to explore the remarkable Sīrah writings in Pashto Language.